Choice of data processing influences practical interpretation of kick leg joint kinetics during the impact phase of ball kicking - Augustus, S.; Hudson, P. E.; Smith, N. (ISBS Proceedings Archive (Michigan), 2020)
The aim of this study was to compare different methods processing kick leg joint moments during the ball impact phase of football instep kicking. Kicking motions and GRFs from eighteen semi-professional footballers were captured by three-dimensional motion analysis (1000Hz) and joint moments were derived using four conventional, and two advanced (time-frequency filter) methods. Ankle, knee and hip moments at ball contact were all different between processing method (P < 0.017), with large pairwise effect sizes (d > 0.8). Choice of data processing influences practical interpretation of ball kicking motions. Filtering `through` the impact phase introduces considerable error, so truncating and extrapolating joint moments before contact should be performed. Use of these methods highlight the importance of: a) training the ankle dorsiflexors for resisting forced plantarflexion upon ball contact, b) developing coaching cues that co-ordinate whole-body action to complement passive knee extension in the final stage of the downswing and c) tailoring training/ coaching of kicking skills to an individual`s preferred movement strategy.